Consumer purchase intention on Boba drinks in Kuching during Covid-19 - Ricky Chee- Jiun Chia; Magdalene Efendi; Venus Khim-Sen Liew (Cogent Business & Management, 2023)
Many businesses were badly impacted as consumer spending habit shifted due to Covid-19 outbreak. The purpose of this study is to investigate consumer purchase intention on Boba drink during Covid-19. By adopting Theory of Planned Behavior, this study explores the influence of perceived behavioral control, subjective norm, and attitude. Importantly, perceived risks is added to the conceptual model to study consumer purchase intention amid Covid-19. Boba drink is a popular beverage in every city in Malaysia, including Kuching, where one could easily spot a Boba drink outlet at almost every corner of the city. A total of 394 complete observations have been obtained from the respondents through a self-administered online survey. The outcome of the analysis uncovered that perceived behavioral control and subjective norm have significant direct relation, while attitude and perceived risks have significant adverse relation with consumer purchase intention during Covid-19. This research offers insights to Boba drink sellers to devise appropriate strategies to market their beverages by targeting consumers' ability to buy the beverage, health-conscious belief, food safety, and attractive promotion to encourage consumers to buy their products during the pandemic.
Keywords: 650; attitude; Boba drink; Consumer purchase intention; Covid-19; perceived behavioral control; perceived risks; subjective norm